Lithiation of phosphorus at the nanoscale: a computational study of LinPm clusters - Rybkovskiy, Dmitry V; Lepeshkin, Sergey V; Mikhailova, Anastasiia A; Baturin, Vladimir S; Oganov, Artem R (Nanoscale, 2024)
Systematic structure prediction of LinPm nanoclusters was performed for a wide range of compositions (0 ≤ n ≤ 10, 0 ≤ m ≤ 20) using the evolutionary global optimization algorithm USPEX coupled with density functional calculations. With increasing Li concentration, the number of P-P bonds in the cluster reduces and the phosphorus backbone undergoes the following transformations: elongated tubular → multi-fragment (with mainly P5 rings and P7 cages) → cyclic topology → branched topology → P-P dumbbells → isolated P ions. By applying several stability criteria, we determined the most favorable LinPm clusters and found that they are located in the compositional area between m ≈ n/3 and m ≈ n/3 + 6. For instance, the Li3P7 cluster has the highest stability and is known to be the structural basis of the corresponding bulk crystal. The obtained results provide valuable insights into the lithiation mechanism of nanoscale phosphorus which is of interest for development of novel phosphorus-based anode materials.Systematic structure prediction of LinPm nanoclusters was performed for a wide range of compositions (0 ≤ n ≤ 10, 0 ≤ m ≤ 20) using the evolutionary global optimization algorithm USPEX coupled with density functional calculations. With increasing Li concentration, the number of P-P bonds in the cluster reduces and the phosphorus backbone undergoes the following transformations: elongated tubular → multi-fragment (with mainly P5 rings and P7 cages) → cyclic topology → branched topology → P-P dumbbells → isolated P ions. By applying several stability criteria, we determined the most favorable LinPm clusters and found that they are located in the compositional area between m ≈ n/3 and m ≈ n/3 + 6. For instance, the Li3P7 cluster has the highest stability and is known to be the structural basis of the corresponding bulk crystal. The obtained results provide valuable insights into the lithiation mechanism of nanoscale phosphorus which is of interest for development of novel phosphorus-based anode materials.